PENGEMBANGAN MODUL PEMBELAJARAN HIMPUNAN DENGAN PENDEKATAN KONTEKSTUAL UNTUK KELAS VII SMP - Agustin, Ririn Dwi (Universitas Islam Malang, 2019)
The purpose of this study was to produce a mathematics module with a contextual approach to junior class VII and describe the material quality modules on the set with a contextual approach to class VII students are viewed from the 3 aspect of validity, effectiveness, and practicality. This type of research is the development of research with ADDIE development model. which includes analysis, design, development, implementation, evaluation. Modules have been developed further validated by the validator 3 is 2 mathematics lecturer Budi Utomo Malang Teachers' Training College and one teacher of mathematics as subject matter experts, media specialists, and linguists. The tests showed an average score of 3:06 in the category invalid and declared effective student questionnaire responses with an average score of 89% were categorized as excellent, and practical dinayatakan modules for which there are instructions for using the module, prerequisites, answer key, etc. From the research it can be concluded THAT module set with a contextual approach feasible to be used as teaching materials for junior high school students of class VII.